RELEVANSI KOMPETENSI DASAR DESAIN PEMODELAN DAN INFORMASI BANGUNAN DENGAN KOMPETENSI KERJA JURU GAMBAR KONSTRUKSI GEDUNG - Melania Agustiana, - (2019)
Basic competency is a set of minimum knowledge, skill and ability that must be achieved by students in mastering concepts or subject matter presented in the classroom for vocational secondary education, especially in the field of construction. The research's objective is to find out how relevance the basic competencies are with the competency of design modeling which is guided by the revised 2013 curriculum with the factual competence of building construction drafter. The development of basic competencies given to students is expected to meet or satisfy the need of job competency of drafter needed in the workforce, today and in the future, and for this reason, efforts to implement basic competencies based on the revised 2013 curriculum in order to be ideal and in accordance with the needs of the field job market construction is certainly an interesting thing to study. A quantitative descriptive with a survey approach was used in this research where the data analysis used was static descriptive quantitative in the form of percentage. The results of this research indicate that the competencies of modeling design and building information have a number of basic competencies divided into several subjects, where most of the basic competencies listed are needed to support the competency of building construction drafters. However, there are still some additional basic competencies provided by partner agencies which is not yet included in the basic competencies prepared by the government. The level of relevance of the basic competencies of design modeling and building information especially at State Vocational School 6 Bandung with job competencies of building construction drafters partner agencies is considered as not really relevant. Keywords: Basic Competency, Work Competence, Desain Modelling and Building Information, Drafter